Metastatic behavior analyses of tetraspanin TM4SF5-expressing spheres in three-dimensional (3D) cell culture environment - Song, Dae-Geun; Kim, Eunmi; Lee, Jung Weon (PHARMACEUTICAL SOC KOREA, 2020)
Cancer metastasis involves diverse cellular functions via bidirectional communications between intracellular and extracellular spaces. To achieve development of the anti-metastatic drugs, one needs to consider the efficacy and mode of action (MOA) of the drug candidates to block the metastatic potentials of cancerous cells. Rather than under two-dimensional environment, investigation of the metastatic potentials under three-dimensional environment would be much pharmaceutically beneficent, since it can mimic the in vivo tumor lesions in cancer patients, leading to allowance of drug candidates analyzed in the 3D culture systems to lower failure rates during the anti-metastatic drug development. Here we have reviewed on the analyses of metastatic potentials of certain cancer models in 3D culture systems surrounded with extracellular matrix proteins, which could be supported by TM4SF5- and/or EMT-mediated actions. We particularly focused the initial events of the cancer metastasis, such as invasive outgrowth and dissemination from the cancer cell masses, spheroids, embedded in the 3D gel culture systems. This review summarizes the significance of tetraspanin TM4SF5 and Snail1 that are related to EMT in the metastatic potentials explored in the 3D gel systems.
Keywords: EPITHELIAL-MESENCHYMAL TRANSITION; IN-VITRO; TM4SF5; LIVER; EXPRESSION; CANCER; INVASION; GENE; OVEREXPRESSION; MICRODOMAINS